Synthesis and Electrochemical Characterization of Sodium-Ion Battery Anode Carbon Biomassa Based on Sunflower Seed Husk (Helianthus annuus) - Dinda Amilia; Syahrul Humaidi; Achmad Subhan; Simanjuntak, Renaldo (Journal of Technomaterial Physics, 2023)
This study aimed to synthesize materials from the carbon biomass of sunflower seed husk (Helianthus Annuus) for sodium ion battery anode. A simple carbonization process was carried out by roasting. The chemical activation process was conducted by adding KOH as much as 4M in 100 mL water solution for 20 hours. Then drying was done in the oven at a temperature of 100ºC for 20 hours, and then continued with the sintering process at a temperature of 900ºC for 2 hours. The sintered results were washed and hydrothermal for 20 hours at 200ºC with 4 mL H2O2 and 1 mL EG in 50 mL Teflon. The resulting acid degree was neutralized (pH ~ 7) with distilled water and then dried at 100ºC for 20 hours. The hydrothermal powder was pulverized using a mortar and pestle and then sieved on a 325 mesh sieve. Anode sheets were prepared by mixing active ingredients: PVDF: Super-P with a composition of 85: 10: 5 by adding 2 ml of DMAC solvent. Electrochemical characterization testing was carried out to see the resulting performance—the results obtained from EIS, CV, and CD show that commercial hard carbon is better.